(untitled) (International Journal of Emerging Trends in Science and Technology, 2017)
This paper investigated the steady three dimensional boundary layer flow of an incompressible viscoelastic nanofluid in the presence of Newtonian heating and chemical reaction. A mathematical formulation has designed for momentum, temperature and nanofluid solid volume profiles. The coupled partial differential equations are solved using the Nactsheim-Swigert shooting technique with the six order Runge-Kutta iteration Method. The results for the dimensionless velocity, temperature, and nanofluid solid volume profiles are discussed with the help of graphs.